Histopathological study of the fertility components of undescended testes in boys of different age group (Journal of Paediatric Surgeons of Bangladesh, 2024)
Background: Undescended testes presents the most common male developmental abnormalities, with infertility frequently observed in unilateral as well as bilateral forms. In that study, we evaluated the histological parameters of Undescended testes based on patient’s age and we recommended for the optimal timing for orchiopexy. Objective: To evaluate the histological parameters of undescended testis and determine the optimal timing for orchiopexy. Methods and Materials: This cross-sectional study included 30 patients with undescended testis(es) in the department of paediatric surgery, BSMMU. After taking relevant history, examination findings and investigation reports of all the study subjects were recorded in the pretested data collection sheet. Then biopsy specimens were collected from the selected testes during orchiopexy and analyzed the parameters including mean tubular diameter (MTD), mean tubular fertility index (MTFI) germ cell count (GCC), Sertoli cell index (SCI) and interstitial fibrosis index (IFI) Results: The MTFI and GCC in children 5-years group was significantly higher than those of any of the other younger age groups (P < 0.05). Other parameters such as testicular volume, MTD and SCI showed no statistically significant difference between the age groups studied. Conclusions: This study revealed that higher number of germ cells exists in the tubules between 6 months and 1 year. After first year of life, the major germ cell parameters deteriorate continuously, thus we recommended that orchipexy should be performed, between 6 months and 1 year but no later than 2 years for preserving future fertility.Journal of Paediatric Surgeons of Bangladesh (2019) Vol.10 (1 & 2): 26-31